2007
DOI: 10.1051/limn/2007021
|View full text |Cite
|
Sign up to set email alerts
|

Benthic diatom communities and their relationship to water chemistry in wetlands of central Italy

Abstract: Diatoms are good environmental indicators and are often the main component of phytobenthos, one of the key groups of organisms recommended by the Water Framework Directive (W.F.D.) for the assessment of ecological status of surface waters. Although diatoms are regularly used as indicators in rivers and in lakes, less is known about the benthic diatom communities in wetland systems, especially in Italy. The main aim of the project was to provide a contribution to the knowledge on distribution, composition and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…For instance, Denys found that epiphytic assemblages from acid lakes are more weakly related to TP concentrations. Despite this, several large‐scale studies suggest that nutrient concentrations are the main variables determining the composition and structure of epiphytic diatom communities . Our results strongly support the conclusion that epiphytic diatom assemblages are useful bioindicators of shallow lake trophic status.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For instance, Denys found that epiphytic assemblages from acid lakes are more weakly related to TP concentrations. Despite this, several large‐scale studies suggest that nutrient concentrations are the main variables determining the composition and structure of epiphytic diatom communities . Our results strongly support the conclusion that epiphytic diatom assemblages are useful bioindicators of shallow lake trophic status.…”
Section: Discussionsupporting
confidence: 82%
“…The present study aims to explore the effect of geographical, morphological and physical/chemical for epiphytic diatom communities in shallow lakes. Previous studies suggest a strong dependence of this community on water chemistry. However, the responses of epiphytic algae to trophic state could be modified by the influence of other factors such as lake altitude or latitude that determine lake characteristics and, therefore, biological community structure .…”
Section: Introductionmentioning
confidence: 74%
“…Sample sizes of 500 cells or lower have been used previously to study the distribution of diatom communities along environmental and spatial gradients (Pan et al ., ; Soininen, ; Della Bella et al ., ; Astorga et al ., ; Wetzel et al ., ). In addition, questions about how diversity changes across disturbance gradients usually require only relative diversities among sites under the different treatment regimens (Hughes et al ., ), and therefore, 500 cells is deemed sufficient to investigate diatoms in reed microhabitats of peatland ditches.…”
Section: Methodsmentioning
confidence: 97%
“…In our study we have observed the pH value in station 1 was 6.8, which is slightly acidic suggesting the starting point of acidification due to pollution (Petrou et al, 2019). High acidification also diminishes silica production in diatoms (Petrou et al, 2019 (Bella et al, 2007). Diatom communities play a significant role in maintaining the water quality in India.…”
Section: Diatom Compositionmentioning
confidence: 62%